2019
DOI: 10.1093/ageing/afz047
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of balance training using a video game console in community-dwelling older adults

Abstract: Background gamification is a potentially attractive option for improving balance and reducing falls. Objectives to assess the effect of balance training using the NintendoTM Wii game console on balance (primary outcome), falls and fear of falling. Design quasi-randomised, open-label, controlled clinical trial in parallel groups, carried out on community-dwelling patients over 70 years, able to walk independently. Participants were assigned 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 17 publications
0
27
1
1
Order By: Relevance
“…The other instruments used were the Functional Reaching Test (33), the Activities-specific Balance Confidence Scale (32,35), the Tinetti balance test and the unipedal stance test (36), the MiniBESTest and the functional gait assessment (34). The center of pressure based balance parameters the were assessed using force plates were velocity (31), sway (29,30,37) and limits of stability (37).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The other instruments used were the Functional Reaching Test (33), the Activities-specific Balance Confidence Scale (32,35), the Tinetti balance test and the unipedal stance test (36), the MiniBESTest and the functional gait assessment (34). The center of pressure based balance parameters the were assessed using force plates were velocity (31), sway (29,30,37) and limits of stability (37).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies showed low risk of bias for sequence generation, and unclear for allocation concealment (1,40). The level of risk of bias was unclear in four studies (29,33,35,37), and high in one study (36).…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 92%
See 3 more Smart Citations